Pendidikan Kesehatan Pada Pasien Diabetes Melitus Tipe 2 yang Mengalami Ulkus Diabetikum Dengan Gangguan Konsep Diri: Citra Tubuh Di Rumah Sakit Tk II Putri Hijau Medan 2021 - Nia Daniaty Siburian; Khairunnisa Batubara; Sri Wahyuni (Jurnal Studi Keperawatan, 2021)
Background: Type 2 diabetes mellitus is a hyperglycemic condition that occurs even though endogenous insulin is available where the insulin levels produced are damaged by insulin resistance in peripheral tissues, the liver produces glucose more than normal, carbohydrates in food are not metabolized properly anymore, eventually the pancreas secretes a large amount of insulin. less than needed. Type 2 Diabetes Mellitus in Indonesia from 2000 experienced a surge of 8.4 million and in 2020 to 21.3 million. Diabetes Mellitus who suffers from diabetic ulcers requires proper care and treatment considering that the healing process is not short. To prevent the severity of injuries, efforts that can be made include good nutritional status, diabetes mellitus control, wound examination, foot care, and diabetic foot exercises. This research method used is descriptive case study. Subjects The research was conducted on 2 patients with 1 case with the same nursing problem, namely body image disorders with the provision of health education. The results of the study were obtained after nursing actions were carried out on patient 1 and patient 2, namely the body image disorder has been resolved by providing health education about the fulfillment of body image. Keywords: Body Image; Health Education; Diabetes Mellitus.